Role of endoscopic ultrasound in liver disease: Where do we stand in 2017? - Saraireh, Hamzeh A (World J Hepatol, 2017)
Endoscopic ultrasound (EUS) was first introduced into medical practice in 1980s as a diagnostic imaging modality for pancreatic pathology. EUS has the unique advantage of combining ultrasound and endoscopy to obtain detailed information of the gastrointestinal tract. Over the past decade, the use of EUS in liver diseases has been increasing. EUS, which was initially used as a diagnostic tool, is now having increasing therapeutic role as well. We provide a review of the application of EUS in the diagnostic and therapeutic aspects of liver disease. We also look at the evolving future research on the role of EUS in liver diseases.